Biosimilars and biologics : implementation and monitoring in a healthcare setting - Lucio, Steven (American Society of Health-System Pharmacists, Inc., 2018)
Get Up to Speed on the Fastest Growing Pharmaceutical Innovation With the Only Guide Written for Pharmacists Among the most anticipated and discussed segments of the pharmaceutical market, biosimilars, are finally beginning to exert a greater impact on practice. To meet the growing need for information, ASHP has published Biosimilars and Biologics. This authoritative, evidence-based resource provides an in-depth perspective on all areas related to these innovative drugs, including: · Legislative/regulatory issues, including the biosimilars act and anticipated FDA guidelines ·